Sustaining effectiveness in global teams: The co-evolution of knowledge management activities and technology affordances - Gibson, Cristina; Dunlop, Patrick; Majchrzak, Ann; Chia, Terence (Institute for Operations Research and the Management Sciences, 2021)
Despite the dynamic nature of knowledge-related activities and the availability of a variety of communication technologies, many global teams habitually use technology in the same way across activities. However, as teams move through cycles of accumulating, integrating, and implementing knowledge, the purposes for communication technologies change. Current theorizing and empirical work on team knowledge management has yet to develop a dynamic theory that incorporates these changes. By conducting a multiwave, mixed method analysis of 48 global teams, we develop a theory of how global teams sustain effectiveness through technology affordance processes. We found that effective teams are those that recognize cues indicating change is necessary and coevolve a symbiosis between new activities, new purposes for interaction, and new uses of communication technologies. This coevolution of purpose with technology use forms new affordances, which enable the team to move on to new knowledge management activities and sustain effectiveness. Our theory more realistically models the dynamics of staying connected while sharing, combining, and implementing knowledge across the globe.